THE LAW OF UKRAINE "ON COPYRIGHT AND RELATED RIGHTS": ANALYSIS OF THE AMENDED PROVISIONS - Voloshchenko, Olga (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2022)
ANNOTATION. Introduction The European integration vector of Ukraine's legislative activity creates a powerful platform for improving domestic legislation. Ukraine, as a party to the Association Agreement between Ukraine and the European Union, undertook to harmonize a large number of domestic legal acts with the legislation of the European Union. The implementation of the set tasks in the outlined areas is achieved by adopting a number of laws that update the existing ones or add novelty to the provisions of the current legislation on intellectual property rights. The most recent "step" towards the approximation of domestic norms to the standards of the European Union was the adoption of a new edition of the Law of Ukraine "On Copyright and Related Rights".Studying the provisions of the latter in general gives a positive impression, taking into account the completeness of the wording of the procedures for acquiring exclusive property rights to individual copyright objects and their compliance with the Directives of the European Union. However, clarification of some provisions of the legislation, in terms of inaccuracies of the categorical apparatus, etc., requires a detailed doctrinal study.Summary of the main results: The article provides the author's vision of the concept of the category "originality of the coposition", which is interpreted through the prism of the author's personal creative work and the presence of the undisputed presumption of legality of the work, which is proven in judicial or extrajudicial dispute resolution procedures. The statement regarding the emergence and existence of a new object of copyright - an NFT work - is proved. The conditions for providing legal protection of an NFT- work are defined, among which a specific one stands out - the need to destroy (destruction) a physical object of art in cases of tokenization of objects of fine art. The author expresses an opinion regarding the nearest prospect of securing such an object of copyright at the legislative level, which is determined by the requirements of practice. An opinion is expressed regarding the possibility of the existence of an NFT work, both as an original and as a derivative composition.Conclusion. The conducted doctrinal study of the main provisions of the Copyright Law "On Copyright and Related Rights" made it possible to review the revised provisions from the "angle" of criticism and identify existing gaps with a list of recommendations for overcoming and eliminating the latter. However, the researched list of outlined issues is not exhaustive and contributes to further development of research in the specified field.